## MichaelaRose 3 years ago Explain how to get x=3 from the equation: (5x - 1)/2 + (-3x - 1)/4 = 9/2

1. saifoo.khan

$\frac{5x-1}{2} + \frac{-3x-1}{4} = \frac92$that?

2. MichaelaRose

Yes

3. saifoo.khan

Ok, find the LCD of the left side. it will be 4. so we can write as, $\frac{2(5x-1) +(-3x - 1)}{4} = \frac92$Agree?

4. MichaelaRose

Okay..

5. saifoo.khan

Now try solving further..

6. MichaelaRose

Simplify the top?

7. saifoo.khan

Yes.

8. MichaelaRose

$(10x-1) +(-3x-1)/4 =9/2$

9. saifoo.khan

a mistake, it's 10x - 2

10. MichaelaRose

oh yeah, that's what I meant haha

11. saifoo.khan

ok.. move forward..

12. MichaelaRose

$7x-3/4 = 9/2$

13. saifoo.khan

good going.. now cross multiply.

14. MichaelaRose

|dw:1335241220694:dw|

15. saifoo.khan

$14x - 6 = 36$

16. MichaelaRose

Oh, okay. So then I add six to both sides?

17. saifoo.khan

Perfect..

18. MichaelaRose

then I divide both sides by 14 and get x=2.78

19. saifoo.khan

seems correct.

20. MichaelaRose

Yay!

21. saifoo.khan

;D

22. MichaelaRose

Thanks! (:

23. saifoo.khan

Welcome.